ANALYSIS OF STRENGTHENING TAXPAYER COMPLIANCE THROUGH THE E-SAMSAT SYSTEM, QUALITY OF SERVICES AND TAX SANCTIONS - Putra, Loist Abdi; Loist, Christine; Efendi, Efendi; Welly, Yerisma; Sudirman, Acai (Unitri Press, 2023)
Purpose: This study aims to analyze the model of strengthening taxpayer compliance through the e-sam sat system, service quality, and tax sanctions at the tax office at the Pematang Siantar Samsat office. Methods: This study used a library and field research design with a quantitative causality approach. Data analysis: Data analysis techniques using the SEM method with Partial Least Squares Modeling (PLS-SEM). Each hypothesis proposed in this study will be tested using SmartPLS Version 3.0 software. The structural Equation Model (SEM) approach based on Partial Least Square is used for hypothesis testing. Results and discussion: The results of the data analysis confirm that the e-samsat system, service quality, and tax sanctions significantly affect taxpayer compliance. Conclusion: With the e-Samsat system, service quality, and appropriate tax sanctions, taxpayers can pay vehicle tax online or through a mobile application. This provides convenience and comfort for taxpayers because they do not need to visit the Samsat office in person. Although the e-Samsat system, service quality, and tax sanctions can play an important role in increasing taxpayer compliance, it is important to remember that an approach focusing solely on these three variables is only partially practical. Education, awareness, and a persuasive approach are also needed to create an environment that supports voluntary compliance by taxpayers. Tujuan: Penelitian ini bertujuan untuk menganalisis model penguatan kepatuhan wajib pajak melalui sistem e-samsat, kualitas pelayanan dan sanksi perpajakan di kantor pajak di kantor Samsat Pematang Siantar. Metode: Penelitian ini menggunakan desain penelitian kepustakaan dan lapangan dengan pendekatan kuantitatif kausalitas. Analisis data: Teknik analisis data dengan menggunakan metode SEM dengan Partial Least Squares Modelling (PLS-SEM). Setiap hipotesis yang diajukan dalam penelitian ini akan diuji menggunakan software SmartPLS Versi 3.0. Pendekatan Structural Equation Model (SEM) berdasarkan Partial Least Square dilakukan untuk pengujian hipotesis. Hasil dan diskusi: Hasil analisis data mengkonfirmasi sistem e-samsat, kualitas pelayanan dan sanksi perpajakan berpengaruh signifikan terhadap kepatuhan wajib pajak. Kesimpulan: Dengan adanya sistem e-Samsat, kualitas pelayanan, sanksi perpajakan yang baik, maka wajib pajak dapat membayar pajak kendaraan secara online atau melalui aplikasi seluler. Hal ini memberikan kemudahan dan kenyamanan bagi wajib pajak karena mereka tidak perlu mengunjungi kantor Samsat secara langsung. Meskipun sistem e-Samsat, kualitas pelayanan, dan sanksi perpajakan dapat berperan penting dalam meningkatkan kepatuhan wajib pajak, penting untuk diingat bahwa pendekatan yang berfokus hanya pada ketiga variabel tersebut tidak sepenuhnya efektif. Pendidikan, kesadaran, dan pendekatan persuasif juga diperlukan untuk menciptakan lingkungan yang mendukung kepatuhan sukarela dari wajib pajak.